2020
DOI: 10.3390/s20102861
|View full text |Cite
|
Sign up to set email alerts
|

Peg-in-Hole Assembly Based on Six-Legged Robots with Visual Detecting and Force Sensing

Abstract: Manipulators with multi degree-of-freedom (DOF) are widely used for the peg-in-hole task. Compared with manipulators, six-legged robots have better mobility performance apart from completing operational tasks. However, there are nearly no previous studies of six-legged robots performing the peg-in-hole task. In this article, a peg-in-hole approach for six-legged robots is studied and experimented with a six-parallel-legged robot. Firstly, we propose a method whereby a vision sensor and a force/torque (F/T) sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A very interesting way of using an FT sensor is presented by Zhao et al (2020). In their work, the peg-in-hole approach for a six-parallel-legged robot is proposed.…”
Section: Related Workmentioning
confidence: 99%
“…A very interesting way of using an FT sensor is presented by Zhao et al (2020). In their work, the peg-in-hole approach for a six-parallel-legged robot is proposed.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, an exploratory gait planning on uneven terrain with touch sensing is proposed as shown in Figure 5 . Exploratory gait incorporates force sensing [ 48 ] on the foot, and it is a planning method in which a robot can adjust gait planning actively when its foot meets obstacles during swing phase. Four three-dimensional force sensors are installed at the foot end-effectors of quadruped robot to achieve the proposed touch sensing.…”
Section: High Terrain Adaptabilitymentioning
confidence: 99%
“…Particularly, in shaft-in-hole assembly, challenges are introduced from the location of the target hole and the smooth insertion of shaft-in-hole. Concerning the location of targets, previous methods relying on pure tactile/force sense [6,7] or hybrid vision-tactile sense [8] can work successfully. Typically, as illustrated in Figure 1a, with the rough pre-positioning of the hole, robots employ force/torque (F/T) sensors to further locate holes exactly to insert the shaft.…”
Section: Introductionmentioning
confidence: 99%
“…With admittance control, robots can adaptively adjust the pose of the end effector toward the hole bottom during the insertion process of shaft-in-hole. Zhao et al [8] showed the successful implementation of admittance control in peg-in-hole assembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation